Pengaruh Label Halal, Kesadaran Halal Dan Citra Merek Terhadap Keputusan Pembelian Produk Kosmetik Wardah Pada Wanita Muslimah Generasi Z Di Kota Jambi - Resi Sutriani; Agustina Mutia; Neneng Sudharyati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Purchasing decisions are one part of the consumer's response to whether or not to buy a product, from several factors that can influence consumers to buy a product where consumers consider halal labels and product brand images that are already known among generation Z women and halal awareness factors that consumers have when they want to make a purchase decision. This study aims to determine and analyze the influence of halal labels, halal awareness and brand image on the purchase decision of Wardah cosmetic products in generation Z Muslim women. The research method used is quantitative descriptive. The results showed that halal labels, halal awareness, and brand image had a positive and significant effect on the purchase decision of Wardah cosmetic products in generation Z Muslim women. In testing the classical assumptions of this study are normally distributed, heteroscedasticity does not occur, and multicollinearity.